Bahasa Inggris - Resti Septikasari (At Turots: Jurnal Pendidikan Islam, 2025)
This study aims to develop e-comic learning media based on religious moderation and the environment for elementary school students in East OKU Regency. The background of this study is the need for media that can improve students' understanding of the values ​​of religious moderation and environmental awareness. The research method used is the ADDIE development model, which includes analysis, design, development, implementation, and evaluation. The results of expert validation show that the developed e-comic has a high level of validity with an average score of 90% for the media aspect and 88% for the material aspect. Limited and extensive trials showed an increase in students' understanding of religious moderation and the environment by 25% and 30%, respectively. Thus, this e-comic is declared effective and can be used in character-based learning in elementary schools. Furthermore, the positive feedback from both educators and students underscores its potential to enhance engagement and comprehension in these critical areas. Future research may explore the integration of interactive elements to further enrich the learning experience.